Sentido e significado de violência na escola para o aluno de 8ª série - Malavolta, Letícia Zavitoski (2005)
Each time more, the contemporary society has being confronted, everyday, with the problems of the violence in yours lives. The increase of the violence cases has taken some people to develop some standards of behavior. Between these standards it is perceived that the young has inspired fear in the society and the society put the blame on the young by the increasing wave of violence. This work was developed with the general purpose to contribute, in part, for the understanding of the violence, so complex and present question in all the space. In this direction, the focus of this work is the violence inside the school. The school, institution, that although still to be known as a protected place, is worry with both the insubordination and the violence of its pupils. The social-historical psychology is the methodology used in this study it was on the grounds of Lev S. Vigotski theory, that historically understands the man inside the culture, or either, product and producer of the society where he lives. Specifically, this research is intend to search the sense and signification of the violence inside school by the pupils eyes. To give voice to these young, to know from them what they think about this condition one study of a focal group was developed with 12 pupils of 7ª and 8ª grade of the basic education of a municipal school in Pirituba, outlying area of the city of São Paulo. A citizen was chose, enters the pupils of the focal group to interview. A half-directed interview was developed within the objectives of the research to recoup the history of the life of an adolescent pupil of 8ª grade of a municipal school. With the results of the analysis of the interview, as well as the information from the focal group it was possible then to understand a small part of this question. The perception that the young is immersed in violence in almost all of the spheres of life, beyond the proper school. They are immersed in violence in the familiar relations, the loving relationships and friendship, in the daily one of the preconception for their ethnical and social class.